Examples of Illusion-Based Hadiths According to Ibn Khuzaymah - May Allah have Mercy on him - an Applied Study (Islamic Sciences Journal, 2023)
ABSTRACT                          Through this research, I concluded that Ibn Khuzayma Muhammad ibn Ishaq ibn Muhammad ibn al-Mughirah al-Sulami al-Nisaburi was born in Safar in the year two hundred and twenty-three and died on the Saturday night after the last dinner of the fifth of Dhul-Qa’dah in the year three hundred and eleven and was buried on Saturday after the first at eighty-eight years. Ibn Khuzaimah, despite the delay of his death to the year (311 AH), is the sheikh of the two imams Al-Bukhari and Muslim outside the two Sahihs, Ibn Khuzaymah did not mention the hadith only in his Sahih, rather he came up with the methods that mentioned this hadith, then he explains the effected path, mentions the reason in it and clarifies  the correct one from these methods, the number of hadiths in which the cause of illusion was mentioned was (15) hadiths, and the number of hadiths in which the word “waham” was mentioned reached (9) hadeeths, and their number with the word delusion was (2) hadiths, and their number with the word “whama” (3) hadiths, and their number with the word “whim” (1) New.
Keywords: The concept of the hadith, the concept of the cause, Ibn Khuzaymah, the hadiths that were motivated by delusion, delusion in the chain of transmission, delusion in the text.